2001
DOI: 10.1054/bjoc.2001.2036
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin and protracted venous infusion of 5-fluorouracil in patients with advanced or relapsed 5-fluorouracil pretreated colorectal cancer

Abstract: SummaryThe purpose of this study was to evaluate the activity and safety of oxaliplatin and protracted venous infusion of 5-fluorouracil (PVI 5-FU) in patients with advanced or relapsed 5-FU pretreated colorectal cancer. 38 patients with advanced or metastatic colorectal carcinoma with documented progression on or within 6 months following 5-FU or thymidylate synthase inhibitor containing chemotherapy were recruited between June 1997 and September 2000. Oxaliplatin (100 mg m -2 ) was given every 2 weeks and PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Table 1 summarizes the reported incidence in various clinical trials in patients with advanced colorectal carcinoma who received a 2‐hour infusion of oxaliplatin in combination with 5‐FU/leucovorin 5–24. Based on these published results, the incidence was 0.55%.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 summarizes the reported incidence in various clinical trials in patients with advanced colorectal carcinoma who received a 2‐hour infusion of oxaliplatin in combination with 5‐FU/leucovorin 5–24. Based on these published results, the incidence was 0.55%.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18][19] In contrast, oxaliplatin with a trans-(R,R)-1,2-diaminocyclohexane (DACH) carrier ligand and oxalato leaving group show less systemic toxicity. 13,[20][21][22] Oxaliplatin overcomes CDDP resistance due to the change in the carrier ligand that alters the type of DNA adducts formed. 13,[20][21][22] This strategy has inspired the generation of many excellent Pt (II/IV) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…13,[20][21][22] Oxaliplatin overcomes CDDP resistance due to the change in the carrier ligand that alters the type of DNA adducts formed. 13,[20][21][22] This strategy has inspired the generation of many excellent Pt (II/IV) complexes. 7,11,23 A wide variety of Pt(II) complexes viz.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the subset of patients benefiting from this treatment strategy was those in whom treatment was interrupted after a response or disease stabilization. Few data exist exploring the role of continuous infusion of 5-FU in bolus 5-FU-resistant colorectal cancer patients, but some studies clearly demonstrated that patients refractory to bolus 5-FU might respond to continuous IV infusion [6, 9, 10, 11]. Recently Andre et al [12] suggested that the reintroduction of infusional 5-FU and oxaliplatin (FOLFOX) in patients pretreated with the same chemotherapy regimen could still show clinical activity in terms of response rate in advanced colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%